2013
DOI: 10.1177/073953291303400207
|View full text |Cite
|
Sign up to set email alerts
|

Print Readers Recall More than Do Online Readers

Abstract: This study of print versus online readers looks at how readers process information in print versus online format. Among the findings is that print news readers remember significantly more news stories than do those who read content online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Despite the popularity of digital editions, to the best of our knowledge, no research has investigated how reading styles of digital editions on tablets differ from printed newspapers and whether what people recall from reading digital editions is different from printed newspapers. Most earlier studies in the field compared printed newspapers with online news sites instead of digital editions (Adam et al, 2007; D’Haenens et al, 2004; Eveland and Dunwoody, 2001, 2002; Jones et al, 2005; Santana et al, 2013; Sundar et al, 1998; Tewksbury and Althaus, 2000). Differences between the printed newspapers and the online news sites in these studies included various content differences (online versions usually contain less information), lay-out differences (headlines and location of articles were different), modality differences (e.g.…”
mentioning
confidence: 99%
“…Despite the popularity of digital editions, to the best of our knowledge, no research has investigated how reading styles of digital editions on tablets differ from printed newspapers and whether what people recall from reading digital editions is different from printed newspapers. Most earlier studies in the field compared printed newspapers with online news sites instead of digital editions (Adam et al, 2007; D’Haenens et al, 2004; Eveland and Dunwoody, 2001, 2002; Jones et al, 2005; Santana et al, 2013; Sundar et al, 1998; Tewksbury and Althaus, 2000). Differences between the printed newspapers and the online news sites in these studies included various content differences (online versions usually contain less information), lay-out differences (headlines and location of articles were different), modality differences (e.g.…”
mentioning
confidence: 99%
“…Research on reading without hyperlinked text has focused on computers and has not demonstrated consistent results in its examination of recall (e.g., Green, Perera, Dance, & Meyers, 2010;Santana, Livingstone, & Cho, 2011), self-judgments of comprehension and memory (e.g., Moore & Zabrucky, 1995), or even comprehension (e.g., Mayes, Sims, & Koontz, 2001). For example, Moore & Zabrucky (1995) demonstrated that although reading times were significantly slower in computer reading, scores of self-judged comprehension did not differ across presentation mode, and participants performed significantly better on scores of overall recall in the computer condition.…”
mentioning
confidence: 99%
“…For example, Moore & Zabrucky (1995) demonstrated that although reading times were significantly slower in computer reading, scores of self-judged comprehension did not differ across presentation mode, and participants performed significantly better on scores of overall recall in the computer condition. In a study of recall across different reading media, Santana et al (2011) showed that the print reading group recalled significantly more news stories, more news topics, and more main points than did computer news readers. In terms of comprehension, Mayes et al (2001) showed no significant difference in comprehension accuracy across the two presentation conditions but found a significant negative correlation between workload and comprehension.…”
mentioning
confidence: 99%
“…Se da alcuni studi emerge come la lettura di testi su schermo intervenga positivamente nel migliorare la comprensione del testo (Dennis et al 2016;Grimshaw et al 2007;Korat 2010); altri non segnalano differenze significative ; Chen e Catrambone 2015; Margolin et al 2013;Norman e Furnes 2016;Porion et al 2016); altri ancora suggeriscono invece che la lettura su schermo possa ostacolare i processi di alto livello che stanno alla base della comprensione (Ackerman e Goldsmith 2011;Ben-Yehudah e Eshet-Alkalai 2014Delgado et al 2018;Kong et al 2018;Latini et al 2019Latini et al , 2020Mangen, et al 2013;Jeong 2012;Sidi et al 2016;Singer Trakhman et al 2017) e che le performances inferiori sullo schermo persistano anche con i dispositivi di ultima generazione (Daniel e Woody 2013;Gu et al 2014). Sembra inoltre che gli studenti che leggono libri di testo elettronici trattengano meno informazioni (Santana et al 2013), abbiano bisogno di più riletture del testo (Noyes e Garland 2008) e ricordino meglio ciò che hanno letto quando hanno la possibilità di annotare il testo su carta, rispetto a quando prendono note sullo schermo (Eden e Eshet-Alkalai 2012).…”
Section: Comprensione E Richiamo Delle Informazioniunclassified